1972
DOI: 10.1530/jrf.0.0300455
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Sows on a Protein-Restricted Diet

Abstract: Two trials with sixty-five sows indicate that severe protein restriction during gestation and lactation significantly impairs subsequent reproductive efficiency. The percentage of sows exhibiting oestrus, the average number of days from weaning to oestrus, and the average ovulation rate and uterine weights were significantly lower in sows fed a low-protein diet. Conception rate and embryo survival to 28 days were not significantly affected. The detrimental effects from protein restriction were more severe in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
11
1
1
Order By: Relevance
“…Others (Shurson et al, 1986;Probert et al, 1999) have also reported similar reductions in body weight during lactation between primiparous and multiparous dams. Negative energy balance during lactation has been linked to delayed weaning-to-estrus interval (Svajgr et al, 1972;Reese et al, 1984;Baidoo et al, 1992;Zak et al, 1998). However in our study, regression analyses did not indicate a relationship between body weight, nor change in body weight, with WEI.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Others (Shurson et al, 1986;Probert et al, 1999) have also reported similar reductions in body weight during lactation between primiparous and multiparous dams. Negative energy balance during lactation has been linked to delayed weaning-to-estrus interval (Svajgr et al, 1972;Reese et al, 1984;Baidoo et al, 1992;Zak et al, 1998). However in our study, regression analyses did not indicate a relationship between body weight, nor change in body weight, with WEI.…”
Section: Discussioncontrasting
confidence: 89%
“…Reports using protein restricted diets during gestation and/or lactation yielded reduced ovulation rate and uterine weights in the subsequent cycle when compared to a normal protein diet (Svajgr et al, 1972;Quesnel et al, 2005). However other studies indicated that lactation body reserve losses had greater impact on ovulation quality and embryo survival at the first post-weaning estrus versus other reproductive parameters such as weaning to estrus interval and pregnancy rate (van den Brand et al, 2000;Clowes et al, 2003aClowes et al, , 2003bPatterson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swick and Benevenga (1977) also noted that restriction of dietary protein intake for pregnant sows had no measurable effect on litter size or birth weight because sows mobilize body reserves to support products of conception. Restriction was, however, found to result in decreased litter growth (Baker et al, 1970) and impaired subsequent reproductive performance (Svajgr et al, 1972). In the present study, supplemental lysine addition to the low-protein gestation diet provided adequate amino acid intake and resulted in normal pig birth weight.…”
Section: Discussionmentioning
confidence: 47%
“…) reported that gravid swine can utilize nu trients more efficiently than nongravid swine. Eward et al (19140 (1965a) 5 Pond et al (1969), Svajgr et al (1970) and Svajgr et al (1972) all reported that the amount of pro tein consumed during gestation did not affect the size of litter farrowed, but did reduce breeding efficiency. Fol lowing a severe protein restriction, some sows failed to exhibit estrus unless pregnant mare's serum was administered to the sows.…”
Section: Review Of Literatube Protein Response On Reproductionmentioning
confidence: 99%